Characterization of Stool Virome in Children Newly Diagnosed With Moderate to Severe Ulcerative Colitis. Issue 10 (21st May 2019) - Tokarz, Rafal; Hyams, Jeffrey S; Mack, David R; Boyle, Brendan; Griffiths, Anne M; LeLeiko, Neal S; Sauer, Cary G; Shah, Sapana; Markowitz, James; Baker, Susan S; Rosh, Joel; Baldassano, Robert N; et al.
Abstract: Background: Viral infections have been suggested as possible triggers for the onset of ulcerative colitis (UC). Methods: We employed VirCapSeq-Vert, a high-throughput sequencing virus capture platform, to examine the stool virome of children with newly diagnosed moderate to severe UC. We surveyed fecal samples collected at presentation, after symptom remission, and from a control group diagnosed with irritable bowel syndrome. Results: Seventy subjects with UC (mean age 13 years, 45 had moderate symptoms, 25 had severe, 69 of 70 had a Mayo endoscopy subscore 2/3) were studied. We detected a wide range of animal viruses that were taxonomically classified into 12 viral families. A virus was present in 50% of fecal samples collected at presentation, 41% of samples collected after remission, and 40% of samples in our control group. The most frequently identified viruses were diet-based gyroviruses. The UC cohort had a significantly higher prevalence of anelloviruses compared with the control cohort. However, we did not identify a single virus that can be implicated in the onset of UC and did not find an association between UC disease severity and viral presence. Conclusion: Presence of virus in stool was not associated with the onset of pediatric UC. Abstract : We used VirCapSeq-VERT, a high-throughput sequencing virus capture platform, to examine the stool virome of children with newly diagnosed moderate to severe ulcerative colitis. We did not identify a link between a viral infection and the onset of ulcerative colitis.